The Role of Motivation, Satisfaction, Discipline, and Environment on Perumdam Tirta Kencana Employees’ Performance - Azhar Latief; Fenty Fauziah (Universitas Medan Area, 2022)
Today, the ability of a corporation to continually maintain and improve the quality of client service is largely dependent on staff performance. Companies with high-performing personnel can assist in maintaining customer satisfaction. Perumdam Tirta Kencana Region III Samarinda City is in severe need of outstanding staff performance to enhance community services and boost enterprise output. The purpose of this study was to determine the impact of motivation, job satisfaction, discipline, and environment on the performance of Perumdam Tirta Kencana Region III Samarinda City personnel. The data analyzed originated from 56 employee questionnaires. Utilizing the technique of saturated sample for data collection (population). Data analysis with Partial Least Square Structural Equation Modeling (PLS-SEM) through SmartPLS version 3.2.9. The results indicated that motivation, job satisfaction, and discipline had a favorable impact on employee performance. The environment has no major effect on employee performance, though. Increased employee motivation, job satisfaction, and work discipline will result in enhanced performance.